2010
DOI: 10.1186/1478-811x-8-18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxic culture conditions on umbilical cord-derived human mesenchymal stem cells

Abstract: Following cultivation of distinct mesenchymal stem cell (MSC) populations derived from human umbilical cord under hypoxic conditions (between 1.5% to 5% oxygen (O2)) revealed a 2- to 3-fold reduced oxygen consumption rate as compared to the same cultures at normoxic oxygen levels (21% O2). A simultaneous measurement of dissolved oxygen within the culture media from 4 different MSC donors ranged from 15 μmol/L at 1.5% O2 to 196 μmol/L at normoxic 21% O2. The proliferative capacity of the different hypoxic MSC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
145
2
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(167 citation statements)
references
References 36 publications
12
145
2
8
Order By: Relevance
“…Several factors, such as inhibition of oxidative phosphorylation due to defects in mitochondrial DNA, dysfunctional Krebs cycle, or inactivation of p53 have been suggested to contribute to the glycolytic switch occurr during cellular expansion and differen-tiation ( Funes et al, 2007). Recently, it has been shown that umbilical-cord derived mesenchymal stem cells adapt their oxygen consumption and energy metabolism to the available oxygen concentrations ( Lavrentieva et al, 2010). In our conditions, HMSCs consumed glucose at higher rates during the first 48 h of expansion.…”
Section: Groupmentioning
confidence: 57%
“…Several factors, such as inhibition of oxidative phosphorylation due to defects in mitochondrial DNA, dysfunctional Krebs cycle, or inactivation of p53 have been suggested to contribute to the glycolytic switch occurr during cellular expansion and differen-tiation ( Funes et al, 2007). Recently, it has been shown that umbilical-cord derived mesenchymal stem cells adapt their oxygen consumption and energy metabolism to the available oxygen concentrations ( Lavrentieva et al, 2010). In our conditions, HMSCs consumed glucose at higher rates during the first 48 h of expansion.…”
Section: Groupmentioning
confidence: 57%
“…A recent study reported a significantly reduced rate of proliferation in severely hypoxic medium with the accumulation of G1 phase cells, 28 which is similar to our findings. Others 20,21 have demonstrated that UCB-derived human MSCs can adapt to a physiologically hypoxic environment by altering their energy consumption and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work examined the ability of MSCs to proliferate and differentiate when exposed to in vitro hypoxic conditions. 20,21 Infusion of MSCs at 3 and 10 days post-hypoxic-ischemic injury was recently shown to enhance cell proliferation, survival and differentiation. 10 It was originally hypothesized that regeneration occurs directly by incorporation of MSC-derived neurons and oligodendrocytes to restore damage.…”
Section: Discussionmentioning
confidence: 99%
“…12 Hypoxia 13 can affect the secretion of paracrine factors, 14 alter gene expression of MSCs 15,16 and enhance proliferation of MSCs. [17][18][19][20][21] The amount of serum present in the culture media also affects stem cell behavior. When MSCs are cultured in 10% serum, some factors may not be present.…”
Section: Introductionmentioning
confidence: 99%